PENGARUH PENERIMAAN PAJAK DAERAH, KONSUMSI RUMAH TANGGA, PRODUK DOMESTIK REGIONAL BRUTO PENDAPATAN ASLI DAERAH (PAD) KABUPATEN/KOTA DI JAWA TIMUR TAHUN 2019-2021 - Doni setyawan, Feri (Universitas Nusantara PGRI Kediri, 2022)
This study aims to determine the effect of local tax revenue, household consumption and GRDP on district/city PAD. Prov. East Java in the 2019-2021 period. The hypothesis was tested using a quantitative method by using the Panel Data Regression sample search method. The results of this study indicate that the significance value of each variable of local tax revenue, KRT, GRDP is very partially influential on regional original income. The dependent variable that is currently being carried out can be added to a new variable, so that further research will expand on the existing variables in the research that has been done.